Enhancing maritime pilotage: exploring the role of negotiation of meaning strategies in training and operations - Batu, Purnama N.F. Lumban; Cahyaningrum, Wida; Bewafa, Sakilah (Intelektual Pustaka Media Utama, 2025)
This study delves into the perspectives and expectations of 37 novice maritime pilots on the application of negotiation of meaning strategies in pilotage operations, aiming to enhance training programs and communication in critical maritime contexts. By conducting qualitative interviews with a mix of experienced and novice pilots, the research sought the role of these strategies in promoting safe and efficient navigation. Participants provided insights through open-ended questions, leading to a thematic analysis that identified recurring themes and patterns in their responses. This approach revealed a detailed view of the communicative strategies employed by pilots, emphasizing their role in navigating the complex maritime environment. The analysis highlighted a series of nuanced communicative challenges faced by novice pilots, pointing to the need for a comprehensive understanding of context and communication strategies in the maritime setting. The findings suggest a shift towards more dynamic, interactive, and scenario-based training methods. Emphasizing the importance of incorporating standard marine communication phrases (SMCP) and participant-driven learning approaches, the study advocates for training that aligns with global standards and the realities of maritime operations, underscoring the importance of enhancing communication efficacy to ensure safety and efficiency in pilotage operations.